RANCANG BANGUN PROTOTIPE SISTEM PENDETEKSI ASAP ROKOK BERBASIS MIKROKONTROLER MENGGUNAKAN SENSOR MQ-2 DILENGKAPI DENGAN EXHAUST FAN - Intania Paramitha1, Ida Ayu Putu; Diafari Djuni, IGAK; Setiawan, Widyadi (Jurnal SPEKTRUM, 2020)
This research is conducted to detect cigarette smoke based on a microcontroller using MQ-2 sensor equipped with an exhaust fan. This system has three status namely good smoke level, moderate smoke level and unhealthy smoke level. The concentration of smoke detected can be monitored by a smartphone, in which the system will send a message via telegram when the room is detected by cigarette smoke. Based on the research that has been done, the system made has been able to send the smoke concentration data to telegram, the detected smoke concentration level and turn on the buzzer and the DC Fan when the smoke concentration status is in moderate level around 100 - 400 ppm and in unhealthy level around > 400 ppm. Furthermore, it has been also able to send the comparison of energy consumption, when both of the fans are off, the energy consumption is 2.42 Wh, and when both of the fans are on, then the energy consumption is 9.44 Wh.